Disease burden, clinical management and unmet treatment need of patients with moderate to severe atopic dermatitis; consensus statements, insights and practices from CERTADE (Central/Eastern EU, Russia, Turkiye AD Experts) Delphi panel - Trzeciak, Magdalena; Rudnicka, Lidia; Arenberger, Petr; Engin, Burhan; L'vov, Andrey; Alper, Sibel; Alpsoy, Erkan; Benáková, Nina; Bobko, Svetlana; Borlu, Murat; Czarnecka-Operacz, Magdalena; Elisyutina, Olga; et al. (Frontiers in Medicine, 2024)
Background There is limited insight into the current disease burden and everyday clinical management of moderate-to- severe AD in Poland, Czechia, Russia, and Turkiye. Therefore, this study aimed to get information-driven insights regarding the current disease burden and clinical management of patients with moderate-to-severe AD with common and differentiating aspects of the patient journey and establish a consensus. Methods In this modified 2-round Delphi panel, 133 questions were asked in total to 27 dermatologists. A consensus was achieved when 70% of the panel members strongly agreed or agreed (or strongly disagreed or disagreed) with an item. Statements with <40% agreement dropped from the Delphi rounds and were not repeated. Results The results state that AD has a significant impact on the quality of life for both patients and their families with social and economic consequences in these countries. While there were significant dissimilarities regarding the current treatment approach by preference order and treatment duration among participants, there was also a high percentage of consensus on literature and guideline-based statements. Current topical therapies and the immune response modifiers were not found to be sufficient by panelists to cover the therapeutic needs of patients with moderate-to-severe AD. Moreover, panelists highlighted the significant burden of adverse events with the off-label use of currently available immunosuppressants. Conclusions These results underlined that there is a significant disease burden with an unmet treatment need for patients with moderate-to-severe AD in Poland, Czechia, Russia, and Turkiye.